Test use and assessment practices of school psychologists in the United States: Findings from the 2017 National Survey. (February 2019) - Benson, Nicholas F.; Floyd, Randy G.; Kranzler, John H.; Eckert, Tanya L.; Fefer, Sarah A.; Morgan, Grant B.
Abstract: Although several studies have examined the specific instruments and procedures used by school psychologists when conducting comprehensive psychoeducational evaluations, the last one was published over 20 years ago (viz., Wilson & Reschly, 1996). Given the substantial theoretical and practical advances in assessment since then, the purpose of the current study was to examine the test use and assessment practices of contemporary school psychologists in the United States. Data from the 2017 National Survey of Assessment Practices in School Psychology revealed that test use and assessment practices have evolved significantly. Much of this change consists of the substitution of tests and practices with limited reliability and validity with those with greater psychometric support. Results of this study also indicate that school psychologists regularly conduct multi-method assessments to prevent, identify, monitor, and remediate child and adolescent learning difficulties and other presenting problems in the schools.